2009
DOI: 10.1007/s00404-009-0965-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and success of fetal programming among women with low and extremely low pre-pregnancy BMI

Abstract: The variation in relative degrees of fetal programming patterns and success observed suggests that underweight mothers are more likely to succeed in programming SGA fetuses rather than any other phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Moreover, while obese women are at greater risk, there is increasing evidence that at least 16% of all women can show signs of metabolic disturbances especially in glucose homeostasis irrespective of body weight [11], as raised glucose alone can increase the risk of offspring obesity [12]. Thus, obesity risk in children linked to maternal nutritional status may occur among women at both extremes, both high [13] and low [14] body mass index (BMI), as well as normal weight women. …”
Section: How Do Maternal Obesity and Diet Influence The Early Nutritimentioning
confidence: 99%
“…Moreover, while obese women are at greater risk, there is increasing evidence that at least 16% of all women can show signs of metabolic disturbances especially in glucose homeostasis irrespective of body weight [11], as raised glucose alone can increase the risk of offspring obesity [12]. Thus, obesity risk in children linked to maternal nutritional status may occur among women at both extremes, both high [13] and low [14] body mass index (BMI), as well as normal weight women. …”
Section: How Do Maternal Obesity and Diet Influence The Early Nutritimentioning
confidence: 99%
“…A N U S C R I P T treatment in prepregnancy had higher SGA rates than those born to normal weight mothers (31.6% vs 26.6%) (Frankenthal et al, 2019). Those associations were similarly existed in spontaneous pregnancies (Tamura et al, 2018;Du et al, 2017;Li et al, 2013;Pan et al, 2016;Salihu et al, 2009;Belogolovkin et al, 2009). Han preformed a systematic review and meta-analyses that included 78 studies and 1,025,784 women and reported that in both developed and developing countries, underweight women were at an increased risk of having an LBW infant (RR=1.48, 95%…”
Section: A C C E P T E D Mmentioning
confidence: 86%
“…Based the theory of epigenetics during pregnancy, underweight mothers may not have the sufficient nutritional ingredients that are required for the optimal realization of epigenetic pathways that drive trophoblastic and fetal growth and development (Belogolovkin et al, 2009). Selection bias and an imbalance of important variables between the groups were major problems in previous observational studies (Sturmer et al, 2006), which usually used traditional regression methods to analyse the association between maternal underweight and perinatal outcomes (Salihu et al, 2009;Kawwass et al, 2016;Dickey et al, 2012).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…There is substantial evidence in the literature which proves that petite women, especially those underweight before pregnancy, give birth to smaller babies. 20 On the other hand, a recently published vast meta-analysis provides evidence that short maternal stature and chronic malnutrition, especially in developing countries, contribute to a higher incidence of SGA. 21 It is hard to draw clear conclusions if that diagnosis is connected to inter-subject variability or the damaging influence of exogenous factors.…”
Section: Discussionmentioning
confidence: 99%